ANALISIS PERAN GURU DALAM MENGATASI PERUNDUNGAN PADA PESERTA DIDIK KELAS 2 SD NEGERI SUNGGINGWARNO 01 KABUPATEN PATI - Bayu Ripto Pratama Bayu; Fine Reffiane; Kiswoyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background that drives this research is that in elementary schools there are still many students who show bullying towards their friends, so education or information about the dangers of bullying behavior is needed. Based on the focus of the problem, the objectives to be achieved in this research are: 1) to determine the forms of bullying behavior in grade 2 students at SD Negeri Sunggingwarno 01 Pati Regency. 2) to determine the role of teachers in overcoming bullying behavior in class 2 students at SD Negeri Sunggingwarno 01 Pati Regency. This qualitative research with a case study approach was used to provide insight into real world conditions and realities, especially the strategies used by teachers to overcome bullying behavior at SD Negeri Sunggingwarno 01 Pati Regency. In this case, first, researchers will conduct interviews with teachers as informants, because teachers are coaches, and create a supportive and comprehensive social context that does not tolerate aggressive and violent behavior at school by students. Based on the results of the research and discussion, it can be concluded from this research that: The types or forms of bullying that occur at SD Negeri Sunggingwarno 01 are divided into three forms, namely verbal bullying: mocking, giving nicknames, calling their friends by their parents' names. physical bullying: kicking, pushing, hitting, breaking other people's objects. Psychological bullying: Embarrassing The role of teachers in preventing bullying carried out at SD Negeri Sunggingwarno 01, namely providing advice to students both individually and classically, building awareness and understanding about bullying and its impact on all parties, especially students, collaborating with parents, filling time. free time with positive things, collaborate with subject teachers to supervise them.